Comparison of anterior and posterior approaches in Treating odontoid fractures: a meta-analysis and systematic review - Bao, Xianguo; Chen, Yingjun; Guo, Chen; Xu, Shuai (Frontiers in Surgery, 2023)
Background Odontoid fractures account for 15%–20% of cervical injuries. Although the operation methods vary in different types, the superiority of overall outcomes of the anterior approach (AA) and posterior approach (PA) in treating odontoid fractures still remains controversial. Thus, a meta-analysis was performed comparing AA and PA for these fractures. Methods The relevant studies were searched in PubMed/MEDLINE, Cochrane Library, EMBASE, China Biological Medicine (CBM), and Wanfang Database from the onset of conception to June 2022. Prospective or retrospective comparative studies on AA and PA for odontoid fractures were screened, referring to fusion rates (primary outcomes), complications, and postoperative mortality rates. A meta-analysis of the primary outcomes and a systematic review of other outcomes were performed; the procedure was conducted with Review Manager 5.3. Results Twelve articles comrising 452 patients were included, and all publications were retrospective cohort studies. The average postoperative fusion rate was 77.5 ± 17.9% and 91.4 ± 13.5% in AA and PA, respectively, with statistical significance [OR = 0.42 (0.22, 0.80), P = 0.009]. Subgroup analysis showed a difference in fusion rates between AA and PA in the elderly group [OR = 0.16 (0.05, 0.49), P = 0.001]. Five articles referred to postoperative mortality, and the mortality rates of AA (5.0%) and PA (2.3%) showed no statistical difference (P = 0.148). Nine studies referred to complications, with a rate of 9.7%. The incidence of complications in AA and PA groups was comparable (P = 0.338), and the incidence of nonfusion and complications was irrelevant. The prevalent cause of death was myocardial infarction. The time and segmental movement retention of AA were possibly superior to those of PA. Conclusion AA may be superior in regard to operation time and motion retention. There was no difference in complications and mortality rates between the two approaches. The posterior approach would be preferred in consideration of the fusion rate.